Functional Topography of Auditory Areas Derived From the Combination of Electrophysiological Recordings and Cortical Electrical Stimulation - Trébuchon, Agnès; Alario, F.-Xavier; Liégeois-Chauvel, Catherine (Frontiers in Human Neuroscience, 2021)
The posterior part of the superior temporal gyrus (STG) has long been known to be a crucial hub for auditory and language processing, at the crossroad of the functionally defined ventral and dorsal pathways. Anatomical studies have shown that this “auditory cortex” is composed of several cytoarchitectonic areas whose limits do not consistently match macro-anatomic landmarks like gyral and sulcal borders. The only method to record and accurately distinguish neuronal activity from the different auditory sub-fields of primary auditory cortex, located in the tip of Heschl and deeply buried in the Sylvian fissure, is to use stereotaxically implanted depth electrodes (Stereo-EEG) for pre-surgical evaluation of patients with epilepsy. In this perspective, we focused on how an anatomo-functional delineation can be achieved using data from electrical cortical stimulation combined with electrophysiological signals recorded during pure tone and syllable listening. We show the differences in functional roles between the primary and non-primary auditory areas, in the left and the right hemispheres, distinguishing more specifically the roles of Heschl’s gyrus (HG), Planum Temporale (PT), the posterior part of the superior temporal gyrus anterior to HG, the posterior superior temporal sulcus (STS), and the region at the parietal-temporal boundary commonly labelled “SPT”. We discuss how these findings help understanding the auditory semiology of certain epileptic seizures and, more generally, the neural substrate of hemispheric specialization for language.